The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/qad.0000000000002227
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and HIV/AIDS

Abstract: Tremendous biomedical advancements in HIV prevention and treatment have led to aspirational efforts to end the HIV epidemic. However, this goal will not be achieved without addressing the significant mental health and substance use problems among people living with HIV (PLWH) and people vulnerable to acquiring HIV. These problems exacerbate the many social and economic barriers to accessing adequate and sustained healthcare, and are among the most challenging barriers to achieving the end of the HIV epidemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
211
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(286 citation statements)
references
References 119 publications
9
211
1
1
Order By: Relevance
“…These results suggest the critical importance of being aware of the psychological health consequences among PLWH. Integrating mental health services into HIV primary care medical appointments may be necessary considering the high burden of mental illness experienced by PLWH [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest the critical importance of being aware of the psychological health consequences among PLWH. Integrating mental health services into HIV primary care medical appointments may be necessary considering the high burden of mental illness experienced by PLWH [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…HIV induces immune activation in the brain which may lead to tryptophan depletion and a resultant reduction in serotonin, thus exacerbating or maintaining depressive symptoms. 59 In addition, several behavioral consequences of depression can impact HIV health outcomes. International studies have shown that depressive symptomatology impedes the activation required to begin and maintain antiretroviral medication and disease management.…”
Section: Mental Health Conditions Of Women Living With Hivmentioning
confidence: 99%
“…The differential power structures that shape social hierarchies are likely instrumental in making certain groups, such as people living with HIV (PLHIV), at higher risk of developing more serious mental health issues [ 4 ]. PLHIV already have a disproportionately higher burden of mental health conditions [ 5 ], yet the impact of the pandemic is presently not well-understood in this potentially vulnerable population.…”
Section: Introductionmentioning
confidence: 99%